A Qualitative Study of Christian Evangelism and Apologetic Strategies Through Youtube Media Among Millennials And Gen Z - Yonathan Suliono; I Wayan Sukra; Oktapianus Parintak; Yohanes T. Agus Indratno (LPPM Universitas PGRI Sumatera Barat, 2025)
Study This aim For analyzing the strategies of Christian evangelism and apologetics through YouTube media among Millennials and Gen Z in Indonesia. Approach study use method qualitative descriptive with design studies case to a number of channel spiritual as well as interview with creators and viewers active. Research results show that effectiveness digital evangelism is defined by three factor main : authenticity message, approach narrative -visual, and ability answer scepticism in a way empathetic as well as rational. The most successful digital apologetics strategies nature dialogic, focused on relevance faith to life real, and use Language communicative bridging faith and reason. YouTube is proven become room mission new for church For present Gospel in a way contextual, creative, and theological for digital generation